REGENERATION OF WHEAT PLANTS FROM WHEAT (Triticum aestivum L. cv CD104) MATURE EMBRYOS - NEIVERTH, Adeline; SILVA, Jussara Berger da; SCHUSTER, Ivan; SANTOS, Marise Fonseca dos; VENDRUSCOLO, Eliane Cristina Gruszka (Scientia Agraria, 2010)
The first step in the application of biotechnology techniques is the establishment of an efficient plant regeneration protocol. The genotype cv CD104 was cultivated in vitro to evaluate ability in calli induction and plantlets regeneration from mature embryos. Two types of explants were used: whole mature embryo (EI) and bi-sected mature embryo (ES). The explants were cultivated in MS medium with decreasing doses of growth regulator (2,4-D), in three distinct phases: induction (0; 1; 2; 4; 8 mg dm-3), maintenance (0; 0,5; 1; 2; 4 mg dm-3) and plant regeneration (0 mg dm-3). After induction, calli were evaluated every 21 days according to their responses of somatic embryogenesis: number of induced calli, calli size, number of germinated embryos, number of calli with green spots and number of regenerated plantlets. Besides the 8 mg dm-3 of 2,4-D produced the best responses in terms of calli induction, the concentration of 1 mg dm-3 showed the best results to the number of plantlets obtained and regenerative efficiency in both EI and ES. Regarding the type of explant, the ES had the best results in terms of ability in calli induction at all concentrations while the EI showed the best results obtained for plantlets regenerated and regenerative efficiency.